2022
DOI: 10.3389/fphar.2022.952169
|View full text |Cite
|
Sign up to set email alerts
|

Luteolin enhances erlotinib’s cell proliferation inhibitory and apoptotic effects in glioblastoma cell lines

Abstract: The epidermal growth factor (EGFR) receptor is frequently overexpressed in glioblastoma multiforme IV (GBM). Increased expression of EGFR leads to increased proliferation, decreased apoptosis, and increased resistance to chemotherapeutic agents. A small molecule called erlotinib inhibits EGFR receptors by binding to their adenosine triphosphate (ATP) binding sites. It is FDA approved to treat a variety of EGFR-mediated cancers. Several clinical trials have explored a combination of erlotinib with other agents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…These concentrations were chosen for evaluating next steps and preparing combined dilutions of drugs. Ratio of 1:1 was used to prepare corresponding dilutions [20,22]. CIs of Erlotinib and Imatinib were acquired (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These concentrations were chosen for evaluating next steps and preparing combined dilutions of drugs. Ratio of 1:1 was used to prepare corresponding dilutions [20,22]. CIs of Erlotinib and Imatinib were acquired (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Study demonstrated that a concentration ratio of 1:1 for each drug in a therapeutic combination reduces excess concentrations and side effects [20,22]. Combination of 8.55 µM drugs in 12h (P > 0.05), 24h ( ** P < 0.01), 36h ( *** P < 0.001), and 48h ( *** P < 0.001) after treatment increased scratch area in treatment groups compared to 0h.…”
Section: Scratch Test and Microscopic Assessment Of U87-mg Cell Migra...mentioning
confidence: 97%
“…The molecular effects of Luteolin were also investigated in relation to the epidermal growth factor (EGF)-induced proliferation of glioblastoma cells and the ability of Luteolin to induce apoptosis in these cells, as EGFR was found to be overexpressed in glioblastomas [ 99 , 100 ]. In their study, Anson et al, 2018 showed that Luteolin significantly decreased the proliferation of glioblastoma cells in vitro in the presence or absence of EGF, wherein Luteolin caused a decrement in the expression levels of phosphorylated Akt, mTOR, p70S6K, and MAPK in the presence of EGF.…”
Section: Anticancer Properties Of Luteolin On Different Cancersmentioning
confidence: 99%
“…Similarly, Powe et al, 2022 showed that Luteolin combined with Erlotinib, an EGFR inhibitor, decreased proliferation and induced apoptosis in glioblastoma cell lines overexpressing EGFR or glioma cells expressing truncated EGFR. Mechanistically, the combination of Luteolin with Erlotinib was found to reduce the phosphorylation of downstream signaling molecules of EGFR, including Akt, NF kappa B, and STAT3 [ 100 ]. Furthermore, it was suggested that the effectiveness of Erlotinib might be enhanced by combining it with Luteolin, which can hold a new therapeutic strategy for glioblastoma [ 100 ].…”
Section: Anticancer Properties Of Luteolin On Different Cancersmentioning
confidence: 99%
See 1 more Smart Citation